Extraction of carrageenan from local seaweeds (Eucheuma cottonii) - Ancheta, Fe C. (1975)
This study was undertaken to determine the effect of varying the time, temperature and pH conditions during the extraction process of the gelling ability and shear stress of carrageenan form a red algae (Eucheuma cottonii). These variables were investigated in Phase I and II, wherein objectives tests showed that the optimum conditions most adequate for the extraction of carrageenan are three hours heating at 100°C and extraction at pH 9. With these conditions, least thermal degradation and hydrolysis were exhibited by the extracts. The last phase, Phase III involved the evaluation of the carrageenan powder. This phase also determined the effect of viscosity on the stabilizing power of carrageenan when incorporated in a chocolate drink. The essential factor in stabilizing the chocolate drink was to increase its viscosity to an extent where the coca particles do not settle. Results of the objective tests showed that the concentration of the carrageenan powder required to stabilize the chocolate drink was 0.3% carrageenan based on the weight of powdered skimmed milk.